A combined experimental and theoretical study of the tautomeric and conformational properties of (5-phenyl-tetrazol-2-yl)-acetic acid methyl ester - Saeed, Aamer (2015)
The tautomeric and conformational properties of a new tetrazole derivative are studied in a combined approach that includes the analysis of the experimental vibrational data together with theoretical calculation methods, especially in terms of natural bond orbital (NBO) population analysis. Moreover, the molecular and crystal structure was determined by single crystal X-ray diffraction. The compound crystallized as the 2-tautomeric form, monoclinic space group P21/c with Z = 4, a = 10.0630(14), b = 8.2879(11), c = 12.8375(18) Å, b = 105.546(3) , V = 1031.5(2) Å3. The tetrazole and phenyl rings are coplanar with the acetate group oriented perpendicular to the plane. The NBO analysis showed that delocalizing interactions of the lpp(N2) lone pair orbital contributes to a strong resonance interactions with both adjacent p⁄(N3@N4) and p⁄(N1@C5) antibonding orbitals of the tetrazole group.